2013
DOI: 10.1515/cclm-2012-0820
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of laboratory tests and practical implications for quality management

Abstract: Patient percentiles offer great potential to assess/monitor the medium- to long-term analytical stability of a test within certain constraints. Differences in analytical quality between assays can significantly affect medical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…This monitoring is a quality indicator of stability of performance of both the laboratory and assay. We used the experience from applying the tool in clinical chemistry for comparison [18][19][20]. As previously explained, the on-line user interface shows the participating laboratory for each instrument the course of the moving median, the mid-to long-term median as well as that from the peer group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This monitoring is a quality indicator of stability of performance of both the laboratory and assay. We used the experience from applying the tool in clinical chemistry for comparison [18][19][20]. As previously explained, the on-line user interface shows the participating laboratory for each instrument the course of the moving median, the mid-to long-term median as well as that from the peer group.…”
Section: Discussionmentioning
confidence: 99%
“…The Committee got by courtesy of STT-Consulting and the Chair (currently Thienpont & Stöckl Wissenschaftliches Consulting) access to 2 new quality management tools to assess whether they could serve the above purpose implied by the FDA. Note that as described elsewhere the tools are part of the overarching "Empower project" [18][19][20][21]. One tool, called the "Percentiler" monitors daily outpatient medians to reflect the stability/variation of performance at the level of the individual laboratory and its peer group.…”
Section: Introductionmentioning
confidence: 99%
“…These range from panels of experts that submit monthly reports [6] to automated systems that resort to summary statistics computed over temporal windows [7,8,9,10,11]. While simple linear models can be used to monitor these complex systems [12], machine learning tools have already proved to be able to generate highly accurate predictions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, just for the intrinsic design of an EQA program, the data are not available in real time. In this issue of Clinical Chemistry and Laboratory Medicine, the team of Thienpont and colleagues, whose remarkable dedication to the improvement of quality, standardization and harmonization of clinical laboratory testing is well appreciated at an international level and by the readers of the journal [10][11][12][13][14], describes a new project aimed to establish a bottom-up cooperation between laboratories and manufacturers, so that they can pursue the common objective of assessing test comparability and stability of laboratory results [15]. The "Empower" project, proposed as an independently operated "online" tool that should monitor comparability and long-term stability between peer groups and laboratories, comprises four pillars: 1) Master comparison with panels of frozen single-donation samples; 2) Monitoring of patients percentiles; 3) Monitoring of IQC data, both across laboratories and manufacturers; 4) Conceptual and statistical education about analytical quality in the medical laboratory and elaboration of actionable experiments for analytical quality management and assurance.…”
mentioning
confidence: 99%
“…It is very important to emphasize that monitoring the patients medians is not a substitute for daily IQC but is a complementary observation tool from patient data that can cover much longer observations time. In a pilot study [12], for measurands with seasonindependent concentrations (i.e., calcium, phosphate, FT4, and TSH), it was demonstrated that laboratories can improve quality assurance by mid-to long-term quality management from patient percentiles. This additional IQC practice, in fact, may help to early alert the laboratory to potential problems with a direct impact and return on clinical decision making.…”
mentioning
confidence: 99%